Association between physical activity and quality of working life among nurses in private hospitals - Xin, Yap Kar; Hamzah, Siti Aishah; Romli, Muhammad Hibatullah (Universiti Putra Malaysia Press, 2024)
Introduction: Nursing is a physically demanding profession; they must be in good physical condition to do the physical tasks such as lifting or positioning the patient. Studies on nurses were mostly carried out in public sectors in Malaysia and investigation among nurses in private sector is limited. Even though there are investigations on physical activity level with quality of life, however, the quality of life explored were general. Therefore, the study aims to determine the association between physical activity (PA) and quality of working life (QoWL) among nurses working in private hospitals. Methods: This is a cross-sectional study. The nurses were recruited by using the snowball sampling method during the COVID-19 pandemic. This study involved 64 nurses (61 female and three male) in private hospitals. Using Google Form, sociodemographic data, physical activity (PA), and quality of the working life (QoWL) were gathered online and analysed using SPSS version 22. PA was evaluated using the Global Physical Activity Questionnaire (GPAQ), whereas QoWL was measured for the Work-Related Quality of Life Scale (WRQoL). Spearman Correlation, the Mann-Whitney Test, and the Kruskal-Wallis Test were applied to determine PA and QoWL. Results: According to the findings, the WRQoL score and age had a significant correlation (p<0.05). The PA was also shown to have a significant on two of the six elements of the WRQoL scale, which represent the control at work and stress at work. The association between physical activity and general well-being also was found significant (p<0.05). Conclusion: This study identified private nurses in Malaysia were physically active and having relatively good quality of working life. The factors such as increase of age among nurses contributes to lower quality of work life.